2022
DOI: 10.1002/lio2.774
|View full text |Cite
|
Sign up to set email alerts
|

Environmental air pollution and chronic rhinosinusitis: A systematic review

Abstract: Objective Chronic rhinosinusitis (CRS) is a highly prevalent and burdensome disease. The pathophysiology is not fully elucidated, but environmental pollutants have been suggested to impact the inflammatory component of the disease process. This review aims to summarize the role of environmental pollution in CRS onset and disease severity. Methods A systematic review was performed following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. PubMed, EMBASE, Cochrane Library, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 62 publications
(99 reference statements)
0
13
0
Order By: Relevance
“…Clarhed et al found that occupational exposure to paper dust, cleaning agents, metal dust, animals, and moisture/moldy/mildew was independently related to having CRS ( 65 ). A recent review carried out by Leland et al found that air pollution (particularly PM) was closely correlated with CRS incidence/prevalence and disease severity ( 66 ). Additionally, Alkholaiwi et al highlighted that CRS symptoms' severity increased with direct contact with allergens, and the greatest proportion of patients with CRS was found among those with blue-collar occupations, such as firefighters, farmers, and fishermen ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clarhed et al found that occupational exposure to paper dust, cleaning agents, metal dust, animals, and moisture/moldy/mildew was independently related to having CRS ( 65 ). A recent review carried out by Leland et al found that air pollution (particularly PM) was closely correlated with CRS incidence/prevalence and disease severity ( 66 ). Additionally, Alkholaiwi et al highlighted that CRS symptoms' severity increased with direct contact with allergens, and the greatest proportion of patients with CRS was found among those with blue-collar occupations, such as firefighters, farmers, and fishermen ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although exposure to environmental and occupational factors such as tobacco smoke, fire smoke and dust exposure have been linked with the prevalence of CRS, the association between the prevalence and severity of CRS and outdoor air pollution is far less understood [ 1 , 4 , 26 ]. According to a recent systematic review, 10 relevant manuscripts have been published before demonstrating higher odds of CRS particularly with PM exposure [ 27 ]. To our knowledge this is the first study using mixed models to describe symptom severity data of CRS patients in relation to outdoor air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%
“…31 A systematic review found that air pollutant exposure, specifically particulate matter and NO 2 , was associated with greater CRS incidence and prevalence, with higher air pollution exposure linked to more severe CRS. 2 Another study conducted in the active duty population found that particulate matter exposure was a major independent contributor to the development of CRS. 32 International studies have also demonstrated that exposure to high levels of air pollution is associated with significantly greater risk for the development of CRS.…”
Section: Air Pollution As a Factor In Healthcare Disparities In Crsmentioning
confidence: 99%
“…Although the exact pathophysiology is not fully understood, environmental pollutants have been shown to be associated with the development of CRS, likely through an increased inflammatory response in the nasal passages. 2,3 Globally, increasing air pollution levels have been linked to a variety of respiratory conditions, including allergic rhinitis, asthma, and CRS. Studies have shown an increased incidence of CRS in areas with higher traffic-related air pollution, which may also be areas with residents of lower SES.…”
Section: Introductionmentioning
confidence: 99%